PENGARUH PENGALAMAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT SOLUSINDO BINTANG PRATAMA JAKARTA SELATAN - Mohamad Hari Wijaya; Hamdi Supriadi (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of work experience and work discipline on employee performance at PT.  Solusindo Bintang Pratama in South Jakarta.  The type of research used is quantitative research.  The research sample was the entire population of 64 people.  The research results show that work experience (X1) has a significant effect on employee performance (Y) with a regression equation value of Y = 10.932 + 0.754.  The correlation coefficient is 0.765, meaning that the two variables have a strong level of relationship.  The determination value is 58.5% while the remaining 41.5% is influenced by other factors.  Hypothesis testing (t test) obtained a calculated t value > t table or (9.355 > 1.999) thus H0 was rejected and H1 was accepted.  Work discipline (X2) has a significant effect on employee performance (Y) with a regression equation value of Y = 24.324 + 0.417. A correlation coefficient of 0.781 means that the two variables have a strong level of relationship.  The determination value is 61,0% while the remaining 39% is influenced by other factors.  Hypothesis testing (t test) obtained a calculated t value > t table or (3.411 > 1.999) thus H0 was rejected and H2 was accepted.  Work experience (X1) and work discipline (X2) have a significant effect on employee performance (Y) with the regression equation value Y = 8.118 + 0.713 + 0.110.  The Correlation Coefficient is 0.771, meaning it has a strong level of relationship.  The determination value is 58.1% while the remaining 41.9% is influenced by other factors.  Hypothesis Test (F Test) obtained calculated F value > F table or (44.715 > 2.760) thus H0 is rejected and H3 is accepted.